Problem analysis for SFK Aneka Enterprise kerepek ordering system / Nurathirah Eliyas - Eliyas, Nurathirah (2017)
This research was about developing a web based ordering system that focuses on problem in order to make sure that the problem stated is the actual one needed to be solved. The SFK Aneka Enterprise problem is low in security because company keeps the ordering data using manual system, lack of data management, difficulty in determining company sales and customer difficult to know product availability and prices. It is a challenge to accurately define requirements as it involves the subject matter expert and to meet the needs of business audiences. Hence, Cause and Effect Analysis (Ishikawa diagram) and Force Field Analysis technique was applied in analysis phase in order to determine the accuracy and correctness of the identified requirement. The project required a web-based system for an administrator to manage the customer account, manage order list, manage product, and manage the company and brand. There are two actors involved in this system which is customer who use the system to make order and admin who operates all in the system. This project used evolutionary prototyping as a method that consist of seven phased which are requirement gathering phase, analysis phase, prototype development phase, client evaluation phase, suggested improved phase, design phase and development phase where each of the phases has its own activities and deliverables. The findings of this project are to develop the ordering system for SFK Aneka Enterprise based on features resulted from Cause and Effect Analysis (Ishikawa diagram) and Force Field Analysis technique.